2012
DOI: 10.1007/s00068-012-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary body armor: technical data, injuries, and limits

Abstract: The introduction of firearms in the fifteenth century led to the continuous development of bulletproof personal protection. Due to recent industrial progress and the emergence of a new generation of ballistic fibers in the 1960s, the ability of individual ballistic protections to stop projectiles greatly increased. While protective equipment is able to stop increasingly powerful missiles, deformation during the impact can cause potentially lethal nonpenetrating injuries that are grouped under the generic term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 37 publications
0
20
0
2
Order By: Relevance
“…The PRISMA flow chart is given in Figure 1. Specifically, 21 conference papers,3 11–13 21–35 12 journals articles,2 4 7 8 10 15 17 18 36–39 six reports,9 14 16 40–42 five articles on websites,20 43–46 three PhD theses,47–49 one standard test method6 and two books5 50 were identified. Data obtained were divided into the following topics: injury mechanisms, wounded personnel, killed personnel and female injuries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flow chart is given in Figure 1. Specifically, 21 conference papers,3 11–13 21–35 12 journals articles,2 4 7 8 10 15 17 18 36–39 six reports,9 14 16 40–42 five articles on websites,20 43–46 three PhD theses,47–49 one standard test method6 and two books5 50 were identified. Data obtained were divided into the following topics: injury mechanisms, wounded personnel, killed personnel and female injuries.…”
Section: Resultsmentioning
confidence: 99%
“…The applied shear stresses may result in tearing of tissue 7 15–17. It is generally accepted that the gross deformation of the chest and the duration and rate at which this deformation occurs affect the injuries observed 7 14 17. However, it is worth noting that the majority of studies reported in the literature that investigate the formation of such stress waves consider hard plates rather than soft armour.…”
Section: Introductionmentioning
confidence: 99%
“…Kevlar from DuPont, Twaron from Teijin) and ultra high molecular weight polyethylene fibers (e.g. Dyneema from DSM) [1]. In today's practice, fiber compositions are extensively employed in flexible armor applications such as bulletproof vests.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the US military utilizes soft armour vests to cover the majority of the torso with a set of four hard armour plates to cover critical organs on the chest, back, and sides. While it has been noted that vests change the distribution of injuries to unprotected areas [130][131][132], there are still gaps in coverage on the torso that would be vulnerable to high-powered rifles. Similarly, there is often little to no protection on the lower body due to the deleterious effect it would have on mobility.…”
Section: Future Of Compound Armour Systemsmentioning
confidence: 99%